Influence of petrominerographic characteristics of limestone rocks in the production of calcium oxide, Bambamarca 2021 (LACCEI, 2024)
This research work has purpose of determining the influence of the characteristics limestone petrominerographic plants in the production of oxide of calcium. The methodology is based on work carried out by field and in laboratories, also by data provided by the owners of each of the lime companies, the work It was made based on 1 limestone sample per company, A total of 5 samples from the lime companies of Bambamarca to carry out two studies, one petrographic and the other geochemical. The results of the analyzes petrominographic surveys, it was possible to identify the most favorable for the production of quicklime, also identified which formation contains the best oxide purity of calcium.